Ecology and Economic Importance of Crows in Different Regions of Uzbekistan - Shokirova Gavkharkhan Nazigulomovna; G‘ulomov Umidjon Olimjon o‘g‘li (Scientific Trends, 2025)
This article explores the ecological roles and economic impact of crows in various regions of Uzbekistan. Crows, especially species such as Corvus corone, Corvus frugilegus, and Corvus monedula, are widespread and adapt well to urban and rural environments. The study analyzes their nesting behavior, feeding ecology, seasonal migration patterns, and interactions with human activities. While crows are sometimes considered pests, they also provide essential ecological services such as scavenging and pest control. The article emphasizes the need for region-specific strategies for managing crow populations to maintain ecological balance and minimize agricultural damage.
Keywords: Crows, Corvus, Uzbekistan, ecology, agriculture, scavengers, pest control, regional biodiversity.